Peranan Guru Bimbingan Konseling pada Anak Usia Dini - Jamilah, Jamilah; Listiani, Meri; Adhaini, Dina; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to explain the influence of guidance and counseling on character development in early childhood. This study uses design research as its methodology. By utilizing design research, it was concluded that not only parents but also BK teachers play an important role in shaping children's character. Providing the right guidance and counseling can have a positive impact on the formation of children's character. As children develop through their developmental stages, they may face various obstacles that hinder their growth. Inconsistencies in child development can arise from problems related to the child itself. Both the family environment and the play environment contribute to the challenges faced by these children. Such problems can lead to behaviors such as arrogance, excessive emotions, anxiety, and so on. School counselors should use age-appropriate counseling techniques to improve their character. Early childhood problems require counseling interventions. Consequently, the implementation of guidance and counseling in early childhood has a very large influence on character development in the future.